Sodium Butyrate Attenuates Taurocholate-Induced Acute Pancreatitis by Maintaining Colonic Barrier and Regulating Gut Microorganisms in Mice - Xiong, Yangyang; Ji, Li; Zhao, Yi; Liu, Ailing; Wu, Dong; Qian, Jiaming (Frontiers in Physiology, 2022)
Background: Acute pancreatitis (AP) damages intestinal barrier, which aggravates AP. Butyrate exhibits anti-inflammatory effects in AP, but it is unknow if such a protective effect is associated with the regulation of gut microorganisms. We aim to investigate the effects of sodium butyrate (SB) on pancreatic inflammation, colonic barrier, and gut microorganisms. Methods: C57BL/6 mice were divided into groups of sham operation (Sham), AP, 200 mg/kg SB intervention (SB-200), and 500 mg/kg SB intervention group (SB-500). Samples were harvested 24 hours after the model was established. The gut microbiota was analyzed using 16S rRNA gene sequencing. Results: Pancreatic infiltration of neutrophils, macrophages, and M2-type macrophages was significantly reduced in the SB-500 intervention group. Supplementation of SB-500 improved colon mucosal histology and the expression of ZO-1 and occluding. The relative abundance of Alloprevotella and Muribaculaceae was increased and that of Akkermansia was decreased in the SB-500 group compared with the AP group. Ruminococcaceae was the most significantly increased species and Prevotellaceae was the most significantly decreased species in the SB-500 group compared with the AP group. Conclusion: High dose of sodium butyrate inhibits pancreatic inflammation probably by maintaining intestinal barrier and regulating gut microbiota in mice with AP.